Self-governance and cooperation - Myers, Robert H. (Oxford University Press, 1999)
Robert Myers presents an original moral theory which charts a course between the extremes of consequentialism and contractualism. He puts forward a radically new case for the existence of both agent-neutral and agent-relative values, and gives an innovative answer to the question how such disparate values can be weighed against each other. The result is a theory of morality which combines a balanced account of its content with a ringing affirmation of its authority